Strengthen the sacral ligament and paravagina by equilibrium control severe pelvic organ prolapse - Zhao, Xin; Niu, Jumin; Liu, Yansong (Frontiers in Surgery, 2023)
Objective To evaluate and analyze the clinical effect of the combination of laparoscopic sacrocolpopexy (LSC), sacral ligament fusion and vaginal suspension in the treatment of severe pelvic organ prolapse Methods A total of 76 cases of patients with pelvic organ prolapse in our hospital between January 2010 to December 2020 were enrolled for research. They had been evaluated pre- and post-operative through pelvic organ prolapse quantification (POP-Q) system, Pelvic Floor Dysfunction Questionnaire Short Form (PFDI-20), Pelvic Floor Function Impact Questionnaire Short form (PFIQ-7), and the Sexual Function Questionnaire Score (PIQS-31). Results All 76 patients went through the procedure successfully without any complications. None of the 76 cases had relapsed. Post-operational results of PFDI-20 and PFIQ-7 were evidently lower than pre-operational results, post-operational results of PIQS-31 were higher than before operation. Conclusions For patients with severe pelvic organ prolapse,a balanced control of the pelvic floor centred on the preservation of the stereoscopic ring around the cervix through revascularization is significantly effective, and has no recurrence after surgery, high patient satisfaction, fewer postoperative complications. It is safe and reliable and worthy of clinical application and promotion.